1966
DOI: 10.1128/aem.14.5.821-825.1966
|View full text |Cite
|
Sign up to set email alerts
|

Production of Guanosine-5′-Monophosphate and Inosine-5′-Monophosphate by Fermentation

Abstract: Production of guanosine-5'-monophosphate and inosine-5'-monophosphate by fermentation. Appl. Microbiol. 14:821-825. 1966.-A biotin-requiring coryneform bacterium which produces glutamic acid was mutated to adenine dependency. The adenine-requiring strain, which excreted inosine-5'-monophosphate (IMP), was further mutated to xanthine dependency. As expected, IMP was also excreted by this mutant. The mutant strain was reverted to xanthine independence in an attempt to obtain a culture with an altered IMP dehydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1967
1967
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…However, when de novo purine nucleotide synthesis is blocked by mutation, the products are nucleosides and free bases (1). Although we and others (8,9,20,23) have shown that Corynebacterium glutamicum mutants excrete intact 5'-nucleotides, all other microorganisms reported thus far excrete breakdown products. Purine auxotrophs of B. subtilis are of special interest because of the massive accumulations of purine intermediates generally observed with this species.…”
mentioning
confidence: 62%
“…However, when de novo purine nucleotide synthesis is blocked by mutation, the products are nucleosides and free bases (1). Although we and others (8,9,20,23) have shown that Corynebacterium glutamicum mutants excrete intact 5'-nucleotides, all other microorganisms reported thus far excrete breakdown products. Purine auxotrophs of B. subtilis are of special interest because of the massive accumulations of purine intermediates generally observed with this species.…”
mentioning
confidence: 62%
“…Another method starts with a nonfunctional mutant from which functional revertants are selected. In some cases, this second mutation simultaneously inactivates the feedback-sensitive site and restores function, originating a deregulated enzyme (5,7,23).…”
mentioning
confidence: 99%